[大學]Prove that A=B

[大學]Prove that A=B

heron0520 於 星期五 二月 04, 2005 8:56 pm


Let A and B be two subsets of E. It there exists a subset C of E such that

Prove that A=B
當把握........

heron0520

 
文章: 406
註冊時間: 2003-03-31

訪客 於 星期六 一月 08, 2011 7:20 pm


A=A∪C-(C-A∩C)=B∪C-(C-B∩C)=B

訪客

 

Re: [大學]Prove that A=B

訪客 於 星期二 一月 11, 2011 12:40 pm


補充一(錯誤)
heron0520 寫到:Let A and B be two subsets of E. It there exists a subset C of E such that...(略)

It there exists...似乎該寫作If there exists...

補充二(其他方法)
設P,Q是2個任一集合,E是宇集合,則
P=P∩E=P∩(Q∪Q')=(P∩Q)∪(P∩Q')
P=P∪∅=P∪(Q∩Q')=(P∪Q)∩(P∪Q')

證明:
A=A

由A配出A∪C
A=(A∪C)∩(A∪C')

由A配出A∩C
A=(A∪C)∩(((A∩C)∪(A∩C'))∪C'),使用結合律
A=(A∪C)∩((A∩C)∪((A∩C')∪C'))

由C'配出A∩C'
A=(A∪C)∩((A∩C)∪((A∩C')∪((C'∩A)∪(C'∩A')))),使用結合律
A=(A∪C)∩((A∩C)∪(((A∩C')∪(C'∩A))∪(C'∩A'))),使用交換律
A=(A∪C)∩((A∩C)∪(((C'∩A)∪(C'∩A))∪(C'∩A')))
A=(A∪C)∩((A∩C)∪((C'∩A)∪(C'∩A')))
A=(A∪C)∩((A∩C)∪C')
同理
B=(B∪C)∩((B∩C)∪C')

∵B∩C=A∩C,B∪C=A∪C
∴(A∪C)∩((A∩C)∪C')=(B∪C)∩((B∩C)∪C')
∴A=B

訪客

 






大學以上數學問題